Hyper-heuristics for power-aware routing protocols - Seredyński, Franciszek; Pilski, Marek (Studia Informatica. System and information technology, 2008)
The idea underlying hyper-heuristics is to discover some combination of straightforward heuristics that performs very well across a whole range of problems. In this paper we describe genetic algorithm-based (GA) approach that learns such a heuristic combination for solving energy-efficient routing problem in mobile ad hoc networks (MANETs).